Effect of diabetes mellitus on periodontal health status, salivary flow rate and salivary pH in patients with chronic periodontitis - Lekaa M Ibraheem; Ban Z Ahmmad; Ayat M Dhafer; Jannat M Dhafer (College of Dentistry/ University of Baghdad, 2020)
Background: Diabetes and periodontitis are considered as chronic diseases with a bidirectional relationship between them. This study aimed to determine and compare the severity of periodontal health status and salivary parameters in diabetic and non-diabetic patients with chronic periodontitis. Materials and Methods: Seventy participants were enrolled in this study. The subjects were divided into three groups: Group I: 25 patients had type 2 diabetes mellitus with chronic periodontitis, Group 2: 25 patients had chronic periodontitis and with no history of any systemic diseases, Group 3: 20 subjects had healthy periodontium and were systemically healthy. Unstimulated whole saliva was collected for measurement of salivary flow rate and pH. All periodontal parameters (plaque index, gingival index, probing pocket depth and clinical attachment level) were recorded for each patient. Results: The results showed that all clinical periodontal parameters were highest in group 1 in comparison with groups 2 and 3. Comparisons between pairs of groups revealed significant differences between groups 1 and 2 for plaque index, gingival index, probing pocket depth and clinical attachment level, and highly significant differences for plaque index, gingival index between groups 2 and 3, and between groups 1 and 3. The salivary flow rate and pH were lower in group 1 compared to groups 2 and 3. Inter-group comparisons of salivary parameters also revealed a significant difference between groups 1 and 2, with a non-significant difference between groups 2 and 3. Conclusion: Type 2 diabetic patients have significantly lower salivary flow rate, pH and present with advanced periodontal destruction compared to healthy patients. Key word: Saliva; periodontitis; diabetes mellitus.